PENGARUH LINGKUNGAN PENGENDAPAN TERHADAP KUALITAS DAN PERINGKAT BATUBARA PADA SATUAN BATUPASIR KUARSA FORMASI BALIKPAPAN - Boy Syamsu; Dian Agus Widiarso; Reddy Setyawan (JURNAL GEOMINERBA (JURNAL GEOLOGI, MINERAL DAN BATUBARA), 2021)
Kutai Kartanegara is one of the areas with quite a lot of coal. The presence of the coal needs to be done further research on the coal depositional environment. The purpose of this research is to determine the effect of the depositional environment on coal quality. Methodology of this research form primary data from the results of field mapping and laboratory analysis and added from previous research. Purpose of the research, it is known that the coal depositional environment is upper delta plain, with limnic conditions, the results of the analysis of coal quality are seen from the ash and sulfur content, A3 and A5 coal seams have higher grades than A2 and A4 seams. The quality of coal in the study area is influenced by the conditions of the depositional environment, namely in the form of constituent materials and fluctuating conditions of seawater and geological conditions that develop.